Construct validity and responsiveness of the University of Wisconsin Running Injury and Recovery Index - Nelson, E. O.; Kliethermes, S.; Heiderscheit, B. (Journal of Orthopaedic & Sports Physical Therapy, 2020)
Objectives: The University of Wisconsin Running Injury and Recovery Index (UWRI) is the first running-specific patient-reported outcome measure (PRO). The UWRI evaluates the key elements runners use to self-assess running ability during recovery. This study evaluated the construct-related validity and responsiveness of the UWRI as an evaluative PRO of running ability following running-related injury (RRI).